Accountability after crisis data, 2010-2019 - Kovras, Iosif (UK Data Service, 2021)
The project ‘Truth, Accountability or Impunity? Transitional Justice and the Economic Crisis’ completed a repository of policies of accountability in response to the post-2008 Great Recession in six European countries (Ireland, Iceland, Greece, Cyprus, Portugal & Spain). The repository included recorded prosecutions of bank executives, office holders and politicians on charges related to white collar crimes and/or corruption in the lead up to the economic crisis. It also includes fact finding commissions (i.e. independent commissions of inquiry and/or parliamentary commissions of inquiry) designed to document patterns of policy and institutional failures that led to the economic meltdown, in the period between 2010-2018. The rationale for developing the repository was, first, to map the range of policies deployed and, second, to investigate potential variations in the national policies. In parallel with the development of the repository, the project included the conduct of approximately 133 confidential semi-structured interviews in Ireland, Iceland, Greece, Cyprus, Portugal, Spain, Washington D.C. (IMF) and Brussels (EU). These included interviews with prosecutors, judges, elected officials (e.g. former Prime Ministers, Ministers, MPs), unelected officials (e.g. policymakers at central banks, relevant ministries, EU bodies, senior IMF executives etc), NGO members, journalists, academics, defense lawyers and other informed stakeholders to understand the rationale and their attitudes towards policies of accountability. There is little emphasis in the extant literature on the role and impact of different mechanisms of accountability in post-crisis settings, so these interviews were expected to shed useful analytical light. Finally, with regards to the case selection six European countries with similar background conditions and exposure to the crisis but different policy responses, each representing a different approach to accountability. The comparative project applies concepts of transitional justice, namely, 'dealing with the past', to investigate how six European societies (Spain, Portugal, Greece, Ireland, Cyprus, Iceland) have come to terms with the origins and consequences of the post-2008 financial crisis. The economic aspects of the crash are well discussed elsewhere; the proposed project argues significant political and legal lessons can be learned from the crisis, but these are missed by viewing it only through an economic lens. Simply stated, transitional justice, a framework developed over the past forty years, considers how national political elites balance popular calls for truth and justice with the pragmatic need for stability in the aftermath of crisis. Prosecutions, truth recovery and amnesties or impunity are much studied mechanisms. Notably, these mechanisms have been deployed in the cases under consideration. Spain and Portugal took only minimal steps to address the causes of the crisis, in effect, pursuing a policy of immunity. Iceland and Cyprus set up ad hoc truth commissions to document the causes of the crisis. Ireland and Greece have prosecuted and convicted a number of bankers and politicians deemed responsible. The project seeks to explain why, despite similar background conditions, societies have formulated different policy responses and to identify the strengths and limitations of each response. This is important. Examining the comparative experience of societies who experiment with policy mechanisms will contribute to the design of better policy responses in times of crisis, decreasing the level of social upheaval, boosting political legitimacy and paving the way for meaningful institutional reform. This project is explicitly about the intersection of politics and law; it focuses on issues of political and institutional failure and the role of law in promoting accountability, responsibility and political learning from economic crises.